2003
DOI: 10.1051/0004-6361:20030961
|View full text |Cite
|
Sign up to set email alerts
|

The stellar content of OMC 2/3

Abstract: Abstract. We have revisited the stellar content of OMC 2 and OMC 3 by means of MIR imaging and NIR photometry; in addition, we have extended the existing (sub)mm maps by a huge 1200 µm map obtained with SIMBA showing new sources and filamentary features for the first time at that wavelength. The MIR data reveal 43 new sources at N and Q which are partly associated with dense condensations at millimetre wavelengths. Six close binary sources could be resolved at locations where existing (sub)mm maps only show si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
103
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(106 citation statements)
references
References 28 publications
2
103
0
1
Order By: Relevance
“…The Class 0 object MMS 4 along with the molecular cores are located more to the East followed by the cold and dense MMS 6 at the most eastern end of Sa 188. A similar trend was found in the FDC of OMC 1 to 3 (Nielbock et al 2003). 4.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The Class 0 object MMS 4 along with the molecular cores are located more to the East followed by the cold and dense MMS 6 at the most eastern end of Sa 188. A similar trend was found in the FDC of OMC 1 to 3 (Nielbock et al 2003). 4.…”
Section: Discussionsupporting
confidence: 84%
“…Finally, there is the most evolved, well studied region around MMS 1 and 2 including V386 Nor. A similar trend of an age sequence along a filamentary cloud was found for OMC 1-3 in Orion A (Nielbock et al 2003).…”
Section: The Protostellar Content Of Sa 187/188supporting
confidence: 78%
“…Column 1 indicates the molecular cloud core, Col. 2 the right ascension, Col. 3 gives the declination, Col. 4 the core mass, Col. 5 the distance, Col. 6 the infrared luminosity, Col. 7 the line width of the transition J = 10-9 of HC 3 N, Col. 8 the HC 3 N column density, and Col. 9 the references. (a) Result obtained from data shown in Table A (2003); (13) Ridge et al (2003); (14) Wang et al (1993); (15) Lada et al (1976); (16) Bergin et al (1997); (17) Morris et al (1976); (18) Tatematsu et al (1993); (19) Peng et al (2012); (20) Chung et al (1991); (21) Gezari et al (1998); (22) Gezari (1982); (23) Sandell (2000); (24) Liu et al (2011); (25) Nielbock et al (2003); (26) Thronson (1978); (27) Bujarrabal et al (1981) found N(HC 5 N) = (5 ± 2) × 10 12 cm −2 for the ridge component, consistent with our values.…”
Section: Hc 5 Nmentioning
confidence: 99%
“…These include continuum observations at several wavelengths (e.g. Chini et al 1997;Johnstone & Bally 1999;Nielbock et al 2003) and various molecular line studies (e.g. Tatematsu 1993;Cesaroni & Wilson 1994;Takahashi et al 2008;Tatematsu et al 2008;Liu et al 2011;Li et al 2012).…”
Section: Parametermentioning
confidence: 99%